Design and Synthesis of 8-Trifluloromethyl-2-Thioquinazolin-(3H)-4-One Nucleosides - Break, Laila M. (Recent Developments in Chemistry and Biochemistry Research Vol. 11, 2025)
Quinazolinone and thioquinazolinone are heterocyclic compounds that occupy a distinct place in the field of medicinal chemistry. Quinazoline-2,4-diones and thioquinazolinones bearing a trifluoromethyl group derivatives were inhibitors of human immunodeficiency virus-1 reverse transcriptase, antagonists at ionotropic glutamate receptors and anticancer compound trifluoromethyl-substituted pyrazole N-nucleoside. 2-Amino-3-trifluloromethyl benzoic acid 1 isothiocyanate KNCS and triethylamine in absolute ethanol was heated under reflux for 3 h. Synthesis of 8-trifluloromethyl-2-thioquinazolin-(1H,3H)-4-one 2. which have been ribosylated by coupling with 1-O-acetyl-2,3,5-tri-O-benzoyl-\(β\) -D-ribofuranose 4 by using the silylation method, afforded \(β\)-anomeric of the benzoylated nucleoside derivatives 5. Debenzoylation of 5 by sodium metal in dry methanol to afford the corresponding free nucleosides 6. The structures of the newly synthesised compounds have been confirmed on the basis of elemental analyses, IR, 1HNMR, 13CNMR and Mass spectral data.The structures of the products 2-6 were established and confirmed.